1993
DOI: 10.1136/gut.34.4.514
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of the defunctioned rectum in ulcerative colitis.

Abstract: Faecal stream diversion may induce inflammatory changes in the defunctioned segment of the large intestine. These changes are predominantly mucosal,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 12 publications
(2 reference statements)
3
33
1
1
Order By: Relevance
“…This feature was not associated with original diagnosis, duration of defunctionalization, or the development of Crohn's disease-like complications. Our findings verify the conclusions of Warren et al, 13 who reported the presence of transmural lymphoid aggregates in excised defunctioned rectums in a much smaller group of patients with ulcerative colitis. They noted no relationship between this phenomenon and Crohn's disease-like outcomes.…”
Section: Morson and Dawson 1 Recognized And Described The Changes Of supporting
confidence: 95%
See 2 more Smart Citations
“…This feature was not associated with original diagnosis, duration of defunctionalization, or the development of Crohn's disease-like complications. Our findings verify the conclusions of Warren et al, 13 who reported the presence of transmural lymphoid aggregates in excised defunctioned rectums in a much smaller group of patients with ulcerative colitis. They noted no relationship between this phenomenon and Crohn's disease-like outcomes.…”
Section: Morson and Dawson 1 Recognized And Described The Changes Of supporting
confidence: 95%
“…They noted no relationship between this phenomenon and Crohn's disease-like outcomes. The present study differed from that of Warren et al 13 by including patients with Crohn's disease and indeterminate colitis and by having much longer clinical follow-up (median, 57 vs. 22 months).…”
Section: Morson and Dawson 1 Recognized And Described The Changes Of contrasting
confidence: 67%
See 1 more Smart Citation
“…1 This group of patients may represent a subset of Crohn's disease that is limited to the colon or has a nonrecurring variety of Crohn's disease. Although there is histologic similarity between defunctionalized ulcerative colitis and Crohn's disease, 18 the possibility exists that the diagnosis of Crohn's disease based on the diverted rectum is the correct one. One patient in our series required pouch excision after developing fulminant anal Crohn's dis- ease in the setting of a previously diverted rectal specimen containing granulomas.…”
Section: Discussionmentioning
confidence: 95%
“…Diverted rectal specimens were not used to differentiate ulcerative colitis and Crohns disease, due to their well reported tendency to nonspecifically mimic the transmural features of Crohns disease. [13][14][15][16] …”
Section: Human Colonic Tissuesmentioning
confidence: 99%